Body Temperature Measurement Tool for Early Detection of COVID-19 Based on Interactive Augmented Reality Technology and Sensor MLX90614: Framework and Prototyping - Subandi, Subandi; Budi Nugroho, Agus Setiyo; Nurkamilia, Nurkamilia; Syahidi, Aulia Akhrian (STMIK Budi Darma, 2021)
The time of the COVID-19 pandemic is still ongoing and it is uncertain when it will end, so contributions from universities are needed in terms of innovation to anticipate the spread of COVID-19. This paper reports on the development of a temperature measurement application for early detection of COVID-19 based on Interactive Augmented Reality (IAR) technology and the MLX90614 sensor by knowing the framework and application prototyping. The application development method used is Extreme Programming (XP) which is a type of Agile Process and implements testing of application features with black-box and the precision of the application. The result of this research is that an application framework is produced, namely, the user opens the IAR camera application then directs the MLX90614 sensor to the target, the target immediately directs his face to the IAR camera, so that the results of body temperature detection can be tracked and visualized the results on the IAR user interface. The IAR camera function is to generate visualization in the form of detection result information into a user interface modeling. Furthermore, for the black-box test results, it was found that all the features of the application were functioning properly and the precision testing results were 94.44% with a very good category. In the future, the features and performance of the application will be improved as well as the efficiency of the form of the device used so that it can be used by the general public.